Sei sulla pagina 1di 8

# Tutorial of Process Control

Lecture 2

## INVERSE LAPLACE TRANSFORM

1
Example (1): find Laplace inverse for F(s)= s ( s+2 )

## Sol: by using partial fraction

=

A1 A2
+
s S+ 2

1
1
A1= s ( s+2 ) = 2
s
1
1
A2= s (s +2) = 2
( s +2 )

1
1 1 1
1
1 1
= l

L1 {F(s)}= l 2 s
s ( s +2 )
2 ( s+2 ) 2

1
= 2

1 2 t
e
2

(s+1)
Example(2): find Laplace inverse for F(s)= = s (s +2)

## Sol: by using partial fraction

A1 A2
Sol: = s + S+ 2
(s +1)
1
A1= s ( s+2 ) = 2
s

Lecture 2

( s+1)
1
s
(s
+2)
A2=
)= 2
( s +2 )

{F(s)}=

l1

1
1
1
1
1

= l1
2 s 2 ( s+2 ) 2
s ( s +2 )

2 t

- 2e

= 2

S +3

s +3
S (s + 7 s+ 10)
2

## Sol: by using partial fraction

(s +3)

= s (s +2)(s+ 5) =
A 1 (s )[
A1

A1
A2
A3
+
s (s +2) + (s +5)

(s 3)
]s 0
s (s 2)(s 5)

3
0.3
10

A 2 (s 2)[
A2

1
6

A 3 (s 5)[
A3

(s 3)
]s 2
s (s 2)(s 5)

(s 3)
]s 5
s (s 2)(s 5)

2
15

Lecture 2

0.3 1 1
2
1

## F(s)= s 6 ( s+2 ) 15 (s+5)

1 2t 2 5 t
L1 { F(s)}= 0.3 e e
6
15
3
Example (4): find Laplace inverse for F(s)= (2 s+ 5)3

Sol:

3
3
= L1
3
8
( 2 s+ 5 )

[( ) ]
1
5
s+
2

3 ( )t
= t2 e 2
8

## Example(5) : find Laplace inverse for F(s)= 3 s2 +12 s2 49

Sol:

L1

] [

8
3
8/3
3/7
+ 2
=L1 2
+ 2 2
3 s +12 s 49
s +12/3 s 7
2

8 1 2
L [ 2 ]
23
s +4

3 1 7
4
3
L 2 2
sin 2t + sinh 7 t
+ 7
=
3
7
s 7

1
Example(6) : find Laplace inverse for F(s)= s 2 s+ 2
2

1
Sol: we can rewrite F(s)= (s1)2 +1
L1 { f ( s ) ] =e t sin t
5( s+2)
Example(7) : find Laplace inverse for F(s)= s (s+ 1)( s+3)
2

Sol:F(s)=

A1 A2 B1 B2
+ 2 +
+
s
s+ 1 s +2
s

## Tutorial of Process Control

Lecture 2

d 2
A1= ds s F ( s) s=0

A1

d 5(s 2)
ds (s 1)(s 3)

s 0

(s 1) 2 (s 3) 2
25

A2

5(s 2)
10
)s 0
(s 3)(s 1)
3

5(s 2)
5
) s 1
2
s (s 3)
2
5(s 2)
5
B2 2
) s 3
s (s 1)
18
B1

F(t)=

25 10 5 t 5 3 t
+ t+ e + e
9
3
2
18

(1) F(s)=
(2) F(s)=
(3) F(s)

6
1
4

+
s s8 s3
19
1
7

+ 3
s+2 3 s5 s

6s
3
+ 2
= s +25 s + 25

(4) F(s)=

5 s+ 2
( s+1 )( s+2 )2

4

Lecture 2

## T0 determines the value of the time function when t=0

lim f (t ) lim sF (s )
t 0

## Example(1): find the initial value of the f(t)=2u(t)+3cost u(t)

2 3s
+
F(s)= s s 2+1

lim f (t ) lim sF (s )
t 0

lim s

[2+ 1+ 12 ]=5
s

s+ 1
Example(2): find the initial value of the F(s)= s+ 2

lim f (t ) lim sF (s )

t 0

lim s

s+ 1
s+ 2

s 2+ s
= s+ 2 =
the numerator polynomial is of lower order than the denominator polynomial.
In case if IVT is applied we get as the initial value.
this is not possible in practical circuits

## Final value theorem:

To determines the steady-state value of the system response
lim f (t ) lim sF (s )

S 0

Example(1): find the final value of the f(t)for the Laplace inverse
1

5

## Tutorial of Process Control

lim f (t ) lim sF (s )

Sol:

Lecture 2

lim s

S 0

S 0

lim

S 0

1
2
s (s + 3 s +3 s+1)
3

1
(s +3 s +3 s+ 1) =1
3

Example(2): find the final value of the f(t)for the Laplace inverse
1

is F(s)= s (s +4)
lim f (t ) lim sF (s )

Sol:

lim s

S 0

S 0

1
1
=
s (s +4) 4

H.W: find the final and initial values of the f(t) for the Laplace
inverse in the following:
1- F(s)=

8
s (s + 2 s+10)
2

'

'

Special function
1- Step function

## Tutorial of Process Control

Lecture 2

2- Pulse function

A
A as
F(s)= s - s e
A
as
= s (1e )

3- Impulse function

Lecture 2

4-Ramp functiom

5-Sine Function